2001
DOI: 10.1161/hc3601.094275
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive End-Organ Damage and Premature Mortality Are p38 Mitogen-Activated Protein Kinase–Dependent in a Rat Model of Cardiac Hypertrophy and Dysfunction

Abstract: Background-Numerous pathological mediators of cardiac hypertrophy (eg, neurohormones, cytokines, and stretch) have been shown to activate p38 MAPK. The purpose of the present study was to examine p38 MAPK activation and the effects of its long-term inhibition in a model of hypertensive cardiac hypertrophy/dysfunction and end-organ damage. Methods and Results-In spontaneously hypertensive stroke-prone (SP) rats receiving a high-salt/high-fat diet (SFD), myocardial p38 MAPK was activated persistently during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 38 publications
(35 reference statements)
6
70
0
1
Order By: Relevance
“…21 p38 inhibition prevents failure-induced cardiac damage caused by fibrosis and apoptosis, [21][22][23] and also tissue damage in other organs. 24,25 Similar results are obtained by genetic ablation of the p38 route (reviewed in ref. 17) while genetic activation in mice of the p38 pathway causes elevated cardiac dysfunction 26 and early death.…”
Section: The P38 Modulesupporting
confidence: 75%
“…21 p38 inhibition prevents failure-induced cardiac damage caused by fibrosis and apoptosis, [21][22][23] and also tissue damage in other organs. 24,25 Similar results are obtained by genetic ablation of the p38 route (reviewed in ref. 17) while genetic activation in mice of the p38 pathway causes elevated cardiac dysfunction 26 and early death.…”
Section: The P38 Modulesupporting
confidence: 75%
“…The introduction of the SFD induces a progressive increase in blood pressure in the SHR-SP within 2 weeks with concomitant depression of endothelial-dependent vasorelaxation, which is followed by evidence of renal dysfunction (albuminuria) and subsequent neurological deficits (Behr et al, 2001;Ma et al, 2001). Thus, it seems that endothelial dysfunction (loss of bioavailable endothelial NO) contributes to the progression and maintenance of chronic hypertension and is a likely determinant of the prothrombotic state and target organ damage observed in this model (Behr et al, 2001;Ma et al, 2001;Yamashita et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…SFD-SHR-SPs have an accelerated mortality rate and were promptly euthanized when signs of morbidity were noted. These signs may include piloerection, lack of grooming, hypersensitivity to sound or touch, loss of appetite in the setting of cachexia, ataxia, decreased movement, and convulsive movements (Behr et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In another study, the activation of p38-MAPK was demonstrated to induce a negative inotropic effect in ARVM by decreasing the response of myofilaments to Ca 2+ during the onset of heart failure (Liao et al, 2002). In addition, during hypertensive endorgan damage, p38-MAPK phosphorylation was found to be related to premature mortality in a rat model of heart failure (Behr et al, 2001). Our laboratory demonstrated that bigET-1 upregulated p38-MAPK, but not ERK phosphorylation, in septic adult rat ventricular myocytes.…”
Section: Signaling and Apoptosis Mechanisms During Simdmentioning
confidence: 98%